The Effect of N Fertilizer Placement on the Fate of Urea-15N and Yield of Winter Wheat in Southeast China - Chen, Zhaoming; Wang, Huoyan; Liu, Xiaowei; Liu, Yongzhe; Gao, Shuaishuai; Zhou, Jianmin (PloS one, 2016)
A field micro-plot experiment using nitrogen isotope (15N) labeling was conducted to determine the effects of placement methods (broadcast and band) and N rates (60, 150 and 240 kg ha-1) on the fate of urea-15N in the wheat-soil system in Guangde County of Anhui Province, China. N fertilizer applied in bands increased grain yield by 15% compared with broadcast application. The N fertilizer application rate had a significant effect on grain yield, straw yield and aboveground biomass, as well as on N uptake and N concentration of wheat. The recovery of urea-15N was a little higher for broadcast (34.0-39.0%) than for band treatment (31.2-38.2%). Most of the soil residual N was retained in the 0-20 cm soil layer. At the N rates of 60 and 240 kg ha-1, the residual 15N was higher for band (34.4 and 108.7 kg ha-1, respectively) than for broadcast application (29.6 and 88.4 kg ha-1, respectively). Compared with broadcast treatment, banded placement of N fertilizer decreased the N loss in the wheat-soil system. Band application one time is an alternative N management practice for winter wheat in this region.